2012
DOI: 10.1109/tcsi.2012.2185305
|View full text |Cite
|
Sign up to set email alerts
|

An LC Quadrature VCO Using Capacitive Source Degeneration Coupling to Eliminate Bi-Modal Oscillation

Abstract: A phase shift technique using capacitive source degeneration (CSD) is presented for LC quadrature voltage-controlled oscillators (QVCO), where capacitively degenerated differential pairs are used to couple the LC tanks to implement a phase-shifted transconductance and negative input resistance to compensate resonator losses, and to minimize the flicker noise contributions. The CSD technique not only introduces excess phase shift to eliminate undesired bi-modal oscillation, but inherently provides a large coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The former reduces power consumption by optimizing LC tank and oscillation amplitude, at the cost of significant degradation of close-in phase noise; the latter achieves excellent phase noise performance by deep switching, while each oscillator consumes more than five times power than proposed. Source degeneration capacitor is used in [19] to eliminate Bi-Modal oscillation and improve phase accuracy of quadrature oscillator, but the improvement of phase noise is limited since only up-conversion of flicker noise from cross-coupled pair is suppressed by the capacitor. Compared to other works which only reduce noise source or suppress conversion gain, the proposed SSB-DC oscillator shows superior close-in phase noise performance and FoM as both ways are adopted simultaneously, without additional consumption of die area and power.…”
Section: Implementations and Measurementsmentioning
confidence: 99%
“…The former reduces power consumption by optimizing LC tank and oscillation amplitude, at the cost of significant degradation of close-in phase noise; the latter achieves excellent phase noise performance by deep switching, while each oscillator consumes more than five times power than proposed. Source degeneration capacitor is used in [19] to eliminate Bi-Modal oscillation and improve phase accuracy of quadrature oscillator, but the improvement of phase noise is limited since only up-conversion of flicker noise from cross-coupled pair is suppressed by the capacitor. Compared to other works which only reduce noise source or suppress conversion gain, the proposed SSB-DC oscillator shows superior close-in phase noise performance and FoM as both ways are adopted simultaneously, without additional consumption of die area and power.…”
Section: Implementations and Measurementsmentioning
confidence: 99%
“…However, the oscillation frequency of a QVCO will depart from the resonance frequency of individual VCO cores because of the coupling mechanisms. The behavior of the two VCO cores including coupling effects can be modeled by a simplified linear model [7], [15] [17], as shown in Fig. 12(a), where provides a negative resistance compensating the energy loss due to the equivalent resistance R of a LC tank, and represents the transconductance of the coupling mechanism between the two VCO cores.…”
Section: E Intrinsic Phase Shift To Avoid Phase Ambiguitymentioning
confidence: 99%
“…Since one VCO core may lead or lag the other VCO core by 90 phase, is introduced to the coupling transconductance. For a conventional QVCO with parallel coupling transistors [24], the frequency deviation can be found with steady state analysis as (15) where the positive or negative sign depends on whether the iVCO leads or lags the qVCO by 90 ;…”
Section: E Intrinsic Phase Shift To Avoid Phase Ambiguitymentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we have shown that for transformer-based oscillators the traditional quality Although, the architecture is claimed to naturally stabilize in the high frequency quadrature mode [36,22], in some cases the oscillator can jump between these two modes during operation, or start up in a mode other than the one intended [50]. Several solutions have been proposed; most involve introducing a phase delay into the coupling path [50][51][52]. While successful in solving the bi-modal oscillation problem, this phase delay reduces the effectiveness of current tuning in QVCOs.…”
Section: Resultsmentioning
confidence: 99%